The Limitations of the Non-Profit Concept in the Foundation Law - Muntaha, Nur Rahmad; Octarina, Nynda Fatmawati (Magister of Law, Faculty of Law, Universitas Islam Sultan Agung, 2025)
This study examines the concept of non-profit in the Foundation Law and its implications for foundations' obligations to implement minimum wages for their employees. Although foundations are oriented towards social goals without seeking profit, they still employ workers who are entitled to employment protection. Dependence on unstable funding sources, such as donations and grants, often poses a challenge in fulfilling these obligations. Using a qualitative method based on normative analysis, this study examines regulations, court decisions, and legal doctrine to determine whether foundations are required to pay minimum wages. The results of the study show that despite their financial limitations, foundations are still required to comply with employment provisions because there are no exceptions in the regulations. Therefore, flexible policies, such as subsidies or incentives, are needed to maintain a balance between the sustainability of foundations and the fulfillment of workers' rights according to legal provisions.